THE PERSPECTIVE OF LIVING HADITH ON WOMEN’S LEADERSHIP IN FATAYAT OF NAHDATUL ULAMA - Hayati, Irma Nur; Sumbulah, Umi (RIWAYAH, 2023)
Islam considers that women and men are the two foundations of society where they have the same role in creating, forming, regulating and utilizing society. Islam has also given various rights, honors and obligations to women in accordance with their honor and dignity as creatures who are responsible before Allah, both towards themselves, their families, society and the state. If Allah had given women the rights and responsibilities, namely to be “human” as servants of Allah, there would be no reason for men to feel superior to the female gender. Men and women are both creatures of Allah who will be held accountable in the afterlife for the rest of their lives. Women’s empowerment and gender issues are very interesting to discuss at the moment. This research discusses the Living Hadith perspective on women’s leadership in the Fatayat Nahdatul Ulama organization in Jobang District, Jember Regency in 2022. This non-formal institution operating in the religious, social and educational fields is phenomenal and has become a trend in society. One of the problems that arises among women’s empowerment activists is their form of involvement in the public sphere which causes controversy. The aim of this research is to explain: what, why and how the Living Hadist perspective on women’s leadership at the Nahdatul Ulama fatayat in Jombang sub-district - Jember district. This research will be studied in more depth by collecting information from various sources; books, internet, social media, and articles. Descriptive qualitative methods were used to analyze the collected data. The results of this research provide enlightenment that women’s leadership from the Living Hadith perspective can explain a new understanding that there is a Watasiyah Principle in the context of women’s Islamic organizational leadership.[Islam memandang bahwa perempuan dan laki-laki merupakan dua landasan masyarakat dimana keduanya mempunyai peranan yang sama dalam menciptakan, membentuk, mengatur dan bermanfaat untuk masyarakat. Islam juga telah memberikan berbagai hak, kehormatan dan kewajiban kepada perempuan sesuai dengan kehormatan dan martabatnya sebagai makhluk yang bertanggung jawab di hadapan Allah, baik terhadap dirinya sendiri, keluarganya, masyarakat dan negara. Seandainya Allah telah memberikan hak dan tanggung jawab kepada perempuan, yaitu menjadi “manusia” sebagai hamba Allah, maka tidak ada alasan bagi laki-laki untuk merasa lebih superior dibandingkan perempuan. Laki-laki dan perempuan sama-sama makhluk Allah yang akan dimintai pertanggung jawaban di akhirat seumur hidupnya. Isu pemberdayaan perempuan dan gender sangat menarik untuk dibahas saat ini. Penelitian ini membahas tentang perspektif Living Hadis tentang kepemimpinan perempuan pada organisasi Fatayat Nahdatul Ulama di Kecamatan Jobang Kabupaten Jember Tahun 2022. Lembaga nonformal yang bergerak di bidang keagamaan, sosial, dan pendidikan ini sangat fenomenal dan menjadi tren di masyarakat. Salah satu permasalahan yang muncul di kalangan aktivis pemberdayaan perempuan adalah bentuk keterlibatannya di ranah publik yang menimbulkan kontroversi. Tujuan penelitian ini adalah untuk menjelaskan: apa, mengapa dan bagaimana perspektif Living Hadist terhadap kepemimpinan perempuan pada fatayat Nahdatul Ulama Kecamatan Jombang – Kabupaten Jember. Penelitian ini akan dikaji lebih mendalam dengan mengumpulkan informasi dari berbagai sumber; buku, internet, media sosial, dan artikel. Metode kualitatif deskriptif digunakan untuk menganalisis data yang dikumpulkan. Hasil penelitian ini memberikan pencerahan bahwa kepemimpinan perempuan dalam perspektif Living Hadis dapat menjelaskan pemahaman baru bahwa terdapat Prinsip Watasiyah dalam konteks kepemimpinan organisasi Islam perempuan].